The regulatory and transcriptional landscape associated with carbon utilization in a filamentous fungus - Wu, Vincent W.; Thieme, Nils; Huberman, Lori B.; Dietschmann, Axel; Kowbel, David J.; Lee, Juna; Calhoun, Sara; Singan, Vasanth R.; Lipzen, Anna; Xiong, Yi; Monti, Remo; Blow, Matthew J.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Filamentous fungi, such as Neurospora crassa, are very efficient in deconstructing plant biomass by the secretion of an arsenal of plant cell wall-degrading enzymes, by remodeling metabolism to accommodate production of secreted enzymes, and by enabling transport and intracellular utilization of plant biomass components. Although a number of enzymes and transcriptional regulators involved in plant biomass utilization have been identified, how filamentous fungi sense and integrate nutritional information encoded in the plant cell wall into a regulatory hierarchy for optimal utilization of complex carbon sources is not understood. Here, we performed transcriptional profiling of N. crassa on 40 different carbon sources, including plant biomass, to provide data on how fungi sense simple to complex carbohydrates. From these data, we identified regulatory factors in N. crassa and characterized one (PDR-2) associated with pectin utilization and one with pectin/hemicellulose utilization (ARA-1). Using in vitro DNA affinity purification sequencing (DAP-seq), we identified direct targets of transcription factors involved in regulating genes encoding plant cell wall-degrading enzymes. In particular, our data clarified the role of the transcription factor VIB-1 in the regulation of genes encoding plant cell wall-degrading enzymes and nutrient scavenging and revealed a major role of the carbon catabolite repressor CRE-1 in regulating the expression of major facilitator transporter genes. These data contribute to a more complete understanding of cross talk between transcription factors and their target genes, which are involved in regulating nutrient sensing and plant biomass utilization on a global level.
CRIS-Team Scopus Importer:2020-03-27
Keywords: DAP-seq; Nutrient; Plant biomass deconstruction; RNA-seq; Sensing; Transcriptional networks